2017
DOI: 10.1111/1750-3841.13688
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Limit Chemical Deterioration of Gilthead Sea Bream (Sparus aurata) Fillets: Coating with Electrospun Nanofibers as Characterized by Molecular, Thermal, and Microstructural Properties

Abstract: Coating of sea bream fillets with thymol loaded chitosan based electrospun nanofibers (TLCN) and chitosan based nanafibers (CN) has been presented a novel approach to delay chemical deterioration. We assessed CN and TLCN with respect of scanting of total volatile basic nitrogen (TVBN), trimethylamine (TMA), thiobarbituric acid (TBA) deterioration during cold storage condition. Electrospinning process was applied to obtain TLCN and CN. Both of nanofibers obtained from biopolymer and bioactive material were cyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 39 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…The potential of the predictive RSM to tailor physical and biological characteristics of chitosan non-wovens has been demonstrated using the example of the membrane zeta potential. The amount of nitrogen atomic surface content has been shown to positively correlate with the measured zeta potential, which is known to be linked with the cell adhesion and proliferation (Chen et al 2011;Jeong et al 2013;Croisier et al 2014) as well as with the antimicrobial activity (Chang et al 2015;Ceylan et al 2017) exhibited by the membrane. Although the model is applicable only under the experimental conditions inside the design space, the potential of RSM in modeling the surface properties of chitosan fibers as an outcome of a multi-parameter process is promising and could pave a way towards rationally designed drug delivery systems or tissue engineering applications based on chitosan non-wovens.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of the predictive RSM to tailor physical and biological characteristics of chitosan non-wovens has been demonstrated using the example of the membrane zeta potential. The amount of nitrogen atomic surface content has been shown to positively correlate with the measured zeta potential, which is known to be linked with the cell adhesion and proliferation (Chen et al 2011;Jeong et al 2013;Croisier et al 2014) as well as with the antimicrobial activity (Chang et al 2015;Ceylan et al 2017) exhibited by the membrane. Although the model is applicable only under the experimental conditions inside the design space, the potential of RSM in modeling the surface properties of chitosan fibers as an outcome of a multi-parameter process is promising and could pave a way towards rationally designed drug delivery systems or tissue engineering applications based on chitosan non-wovens.…”
Section: Discussionmentioning
confidence: 99%
“…Flow rate, concentration of used material(s), high voltage level, distance between collector and Taylor cone play a key role on morphological properties of nanofibers obtained by electrospinning technique. As stated by Ceylan, Sengor, and Yilmaz (2017b), flow rate, applied high voltage and distance for obtaining chitosan-based nanofiber that had 93.43 nm average diameter was adjusted to be 0.5 ml/hr, 20 kV and 12 cm, respectively. In addition, Li et al (2015) FIGURE 1 Differential scanning calorimetric profiles (heat flow vs. temperature) of PS nanofiber FIGURE 2 Differential scanning calorimetric profiles (heat flow vs. temperature) of PS-loaded LR-based nanofiber reported that the average diameter of NiO / ZnO nanofibers was less than 100 nm.…”
Section: Morphological Characterization Of Nanofibersmentioning
confidence: 99%
“…Therefore, researchers in scientific area are recently tending to obtaining lower-scale material as food surface coating. In this respect, nanotechnological applications providing larger contact area on food surface (nanofibers, nanoencapsulation, nanoemulsion, nanotube, and nanoparticule) have been emerged to delay the microbial spoilage and chemical deterioration of food (Abdou, Osheba, & Sorour, 2012;Ceylan, Sengor, Sagdıc, & Yilmaz, 2017a;Ceylan, Sengor, & Yilmaz, 2017b;Rai, Pandit, Gaikwad, & Kövics, 2016;Yılmaz et al, 2016). Except nanoencapsulation technique, some studies related to encapsulation such as microencapsulation (Jafari, Assadpoor, He, & Bhandari, 2008) were revealed, but most of them included direct preservation of fish oil.…”
Section: Introductionmentioning
confidence: 99%
“…With the awareness of healthy food consumption in recent years, conservation techniques based on alternative biological principles have gained importance. It has focused on the studies of various edible film coatings in freshly consumed foods, which are particularly sensitive such as meat, chicken, and fish (Ceylan, ; Ceylan, Gulgun, Şengör, & Yılmaz, ; Ceylan, Şengör, Sağdıç, & Yılmaz, ; Ceylan, Şengör, & Yılmaz, ).…”
Section: Introductionmentioning
confidence: 99%